Risk of Chrysantemum Flower Supply Chain in Central Java Province and Yogyakarta Special Region - Cahyaningtyas Putri Suhita; Irham Irham Irham; Arini Wahyu Utami (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2020)
The distribution of chrysanthemum flowers from Bandungan District to consumers in the city can be at risk of damage. This study aims to determine the risk sources and types in the chrysanthemum supply chain; analyze risks probability and impact risk as well as risk capacity management among the chrysanthemum supply chain agents; and identify the risk priority in the chrysanthemum supply chains based on the level of loss and vulnerability. Data collection was conducted between April and September 2019 at Bandungan sub-distric Semarang distric. This study interviewed fifty farmers, fifteen middlemen, eight suppliers, and twentyfive florists. Additionally, there were also interviewed three expert regarding chrysanthemum faming. These were the leader of Astha Bunda Kalirang farmers group, the head of marketing division of Astha Bunda Kaliurang Farmers Group, and staff on BPTP in Yogyakarta. Data was analyzed using Rapid Agricultural Risk Assessment (RapAgRisk). Results showed that there were six risk sources and 23 risk types that were present along the chrysanthemum supply chain. Six risks source such as natural hazard, weather, market, management and operational, logistical and infrastructure, and plant biological and environmental. Supply chain actors who have the highest risk are at farmer level.